KEANEKARAGAMAN JENIS GASTROPODA PADA EKOSISTEM HUTAN MANGROVE DESA SEBUBUS KECAMATAN PALOH KABUPATEN SAMBAS - Ernawati, Lisa; Anwari, M Sofwan; Dirhamsyah, M (Universitas Tanjungpura, 2019)
Gastropod is one the mollusk phylum that can adapted at the mangrove ecosystem. Gastropod are organisms that have an ecological role as forming detritus. The study aimed to examine species diversity of gastropods in the mangrove forest ecosystem of Sebubus Village, Paloh District, Sambas Regency. The study was conducted in April 2019, using the survey method. Observations found 6 families and 16 species of gastropods in the mangrove ecosystem. Gastropods species are Chicoreus capucinus, Nerita balteata, Neritina cornucopia, Nerita violacea, Cerithideopsilla alata, Cerithidiopsis quoyii, Cerithidea obtusa, Littoraria scabra, Littoraria undulata, Littoraria carinifera, Nassarius dorsatus, Cassarius dorsatus, Cassidula aurisfelis, Ellobium aurisjudae, Cassidula nucleus, Pythia plicata, and Ellobium gangeticum. Species diversity index of gastropod in zone 1 = 0.83, zone 2 = 0.73 and zone 3 = 0.79 in the low category. Species abundance index of gastropod in zone 1 = 15.3, zone 2 = 10.5, zone 3 = 15.8.Â Species evenness index of gastropod in zone 1 = 0.32, zone 2 = 0.30 and zone 3 = 0.30 categorized as low. Species dominance index of gastropod in zone 1 = 0.20, zone 2 = 0.28 and zone 3 = 0.25 are categorized as low. Species similiarity index of gastropod in zone 1 and 2 = 91.67%, zone 2 and 3 = 80.00%, zone 1 and 3 = 81.48 are categorized very high.Keywords: Diversity, Gastropods, Mangrove Ecosystems